Difference in Image Information Between DWI Sequence and DWI Blade for Optimization of Axial Brain - Bintang Kukuh Iman Setyabudi; Hernastiti Sedya Utami; Fani Susanto; Kusnanto Mukti Wibowo (UM Purwokerto Press, 2024)
Background: Diffusion Weighted Image (DWI) sequence that utilizes the movement of molecules due to random thermal motion. The aim of this research is to determine the difference in image information between DWI sequence and DWI BLADE on axial brain MRI images for optimization and to find the most optimal sequence between DWI and DWI BLADE on axial brain MRI images. Method: This study used a quantitative experimental research that aims to determine image information and optimize brain MRI examinations between DWI sequence and DWI BLADE using the MRI Siemens Magnetom Amira 1.5 T at Dr. Oen Kandang Sapi Hospital Solo in May-June 2023. The sample consisted of 11 MRI assessments through visual grading analysis to provide interpretations related to image clarity information, thus obtaining the optimal use of DWI and DWI Blade sequences. Results: Based on the research and discussion results, it can be concluded that there is a difference in anatomical image information between DWI sequence with BLADE and without BLADE on axial brain MRI examinations, with a significance value of 0.00 (p<0.05), indicating a difference in anatomical image information in the cortex cerebri, thalamus, cerebellum, basal ganglia, and a significance value of 1.000 (p<0.05) for artifact information, indicating no difference in artifact image information between DWI sequences with BLADE and without BLADE. Conclusion: DWI BLADE sequence provides better anatomical image information compared to DWI sequence without BLADE in axial brain MRI examinations.